The Restitution of Children as Victims of the Crime of Obscenity in the Principles of Restorative Justice - Randi Hernanto Madu (Estudiante Law Journal, 2020)
Abstract: The purpose of this study is to find out how the problems that become obstacles in fulfilling the restitution of children as victims of criminal acts of obscenity through the settlement of cases with the principle of restorative justice. The type of research used is Empirical Law research, then the data is analyzed descriptively or provides an overview or explanation of the subject and object of research as the results of the research conducted. The results of this study indicate that the process of resolving cases with the principle of restorative justice by the Gorontalo Police is applied on the basis of the wishes of the victims who have wanted a family settlement with the condition that they want compensation. There is a peace agreement between the two parties, the police issued a letter of termination of the investigation as a result of restorative justice which was recorded in the register book in book B-19 as a case that was terminated through restorative justice. Furthermore, on the fulfillment of restitution for children as victims of criminal acts of obscenity by the Gorontalo Police in collaboration with the Witness and Victim Protection Agency (LPSK). some of the victims asked for their children to be married, sent to school, and other losses. However, there are several things that become obstacles in the process of fulfilling restitution for victims of sexual abuse, which include the desire of the victim, the economic factor of the perpetrator, the communication factor, and the factor of the substance of the legislation. Some of these factors have an impact on the fulfillment of restitution which is hampered and takes time.